2012
DOI: 10.1093/treephys/tps095
|View full text |Cite
|
Sign up to set email alerts
|

A gene expression analysis of cell wall biosynthetic genes in Malus x domestica infected by 'Candidatus Phytoplasma mali'

Abstract: Apple proliferation (AP) represents a serious threat to several fruit-growing areas and is responsible for great economic losses. Several studies have highlighted the key role played by the cell wall in response to pathogen attack. The existence of a cell wall integrity signaling pathway which senses perturbations in the cell wall architecture upon abiotic/biotic stresses and activates specific defence responses has been widely demonstrated in plants. More recently a role played by cell wall-related genes has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Using in vitro micro-propagated apple plantlets, we have shown effects on gene expression and biochemical alterations related to phytoplasma infection. Although the in vitro system does not allow to selectively analyze different tissues or to evaluate the seasonality of gene expression and/or biochemical changes, our results and those from previous investigations show that it represents a useful system for a generalized assessment of transcriptional changes following phytoplasma infection [10].…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Using in vitro micro-propagated apple plantlets, we have shown effects on gene expression and biochemical alterations related to phytoplasma infection. Although the in vitro system does not allow to selectively analyze different tissues or to evaluate the seasonality of gene expression and/or biochemical changes, our results and those from previous investigations show that it represents a useful system for a generalized assessment of transcriptional changes following phytoplasma infection [10].…”
Section: Discussionmentioning
confidence: 59%
“…The molecular mechanisms involved in the interaction between phytoplasmas and host plants are so far largely unknown and only recently some gene expression changes have been identified [2,6,8,10,17]. Using in vitro micro-propagated apple plantlets, we have shown effects on gene expression and biochemical alterations related to phytoplasma infection.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Therefore, abiotic and biotic stresses are often physiologically interrelated and can induce similar responses at the level of cell wall. Moreover, it was recently revealed that local and systemic acquired resistance to pathogens could be regulated by the same genetic system as the systemic acquired acclimation to abiotic stress [9,10] and that a set of genes participating in metabolism of cell wall polymers is involved in the plant defence responses [3,11,12]. A hardening of winter crops during autumn is a factor inducing the genotype-dependent resistance to infection [2,10].…”
Section: Introductionmentioning
confidence: 99%